Félix Antônio Lisboa: sua vida e trajetória entre o sacerdócio e a arte escultórica - Fábio Mendes Zarattini (2020)
Minas Gerais displays great diversity of images, carvings, paintings, objects full of culture, history and religiosity. Countless artisans responsible for this rich sacred production still await practically in anonymity and need to be researched and rediscovered. The present work contemplates the study of the sculptor, Félix Antônio Lisboa, his life and trajectory between the priesthood and the sculptural art. Similar to other colonial sculptors, the attribution of works to Father Félix, a half brother of Antonio Francisco Lisboa, is made difficult by the scarcity of documentary and historical sources that prove the work between religious brotherhoods, artists and craftsmen. This study was based on a literature review about his biography, and trajectory in the priesthood, at first glance, his most recognized and relevant occupation, since after his formation at Our Lady of the Good Death Seminary in Mariana, he acted as “priest of Saint Peter ”in the Secular Clergy from 1778 until his death; he was a member of the Brotherhood of Our Lady of Mercy of Forgiveness from 1782 to 1787, of the Venerable Third Order of Penance of San Francisco from 1781 until his death; he held the position of Master Novice General Definitor e Comissar in the Third Franciscane Order. In addition to field research, documentary and historical records of his works and other attributions performed, in order to contemplate his performance in the art of carving. Through photocumentation performed in loco, the presence of shards or styles in his artistic production was analyzed. For this, the characteristics of a specific group of already documented polychrome wood carvings and other attributed works of images present in churches of the cities of Piranga, Ouro Preto, Belo Vale, São Brás do Suaçuí and Pará de Minas were studied. The work prioritized the formal analysis in favor of the need to define the styles and the understanding of the characteristics of his work in polychrome and gilded wood carvings, St. Peter and St. Paul apostles, occupants of the lateral niches of the main altarpiece of the Bom Senhor Jesus de Matosinhos, in Piranga, former village of Bacalhau in Minas Gerais. As a result, it was noticed that most of the formal aspects present in his attributed works differ from those found in his documented production, not referenced by documents, and mainly disconnected from their respective formal analyzes and style. Several documents, receipts and records provoke questions about the information contained, which indicates that much remains to be clarified regarding their production, artistic training and work in workshops. Due to the scarcity of documented or recognized works, it is difficult and complex to map their production in the imaginary. Therefore, the dissertation critically analyzed and raised hypotheses about the documented collection and questioned current attributions to this sculptor, drawing considerations regarding the artificer, giving due importance to his legacy in sculpture from this state of Brazil.